Social Capital, Technological Empowerment, and Resilience in Rural China - Chao Wang (MDPI AG, 2021)
In the post-pandemic era, the need for resilient and flexible COVID-19 prevention strategies in rural areas has become increasingly prominent. Based on a sample of 2229 rural residents nationwide, the Structural Equation Model was adopted to analyze the influence of social capital and technological empowerment on pandemic resilience in rural areas. The proportion of diversity, adequacy, and effectiveness of pandemic prevention measures taken by communities was about 57%. Social capital (0.667) and technological empowerment (0.325) had a significant positive impact on rural resilience and pandemic prevention. Social capital plays a mediating role between technological empowerment and pandemic resilience in rural areas. The risk of disease in society stimulates the inherent social capital factors in villages, with the individual social network generating strong social support. Technological empowerment can not only provide new methods for the connection of social capital, but also bring new means for rural authorities to improve their governance capabilities. Social trust in social capital plays an important role in rural resilience and pandemic prevention. The indirect effect of technological empowerment through social capital on pandemic resilience is greater than its direct effect. Social capital construction is the key to rural resilience and pandemic prevention.